Anatomic variations of the extrathoracic course of the intercostobrachial nerve and its clinical significance - Nayak, Soubhagya Ranjan; Banerjee, Smita Singh (Asian Journal of Medical Sciences, 2018)
Background: The intercostobrachial nerve (ICBN) can present anatomic alterations in its course, but in general it originates as a lateral branch of the second intercostal nerve and penetrates the axilla, in the mid axillary line. Its communication with brachial plexus (BP) is of clinical importance. Neurotization and nerve grafting procedures have renewed interest in the communications of peripheral nerves, like that of between BP and ICBN. Aims and Objective: The current study was conducted with an aim to observe the variation in the origin of extra thoracic course of the ICBN and its connection with the components of BP. Materials and Methods: One hundred thirty hemi-thoraxes of 65 adult cadavers (35male & 30 female) of Indian origin were dissected. After removal of the skin and superficial fascia, the ICBN was identified from its origin. The point of emergence from the intercostal space and its communication with BP was noted and photographed. Results: Extrathoracically, ICBN originated from the 2nd intercostals space in 100% specimens. Additionally ICBN originated from the 1st intercostals space in 3.8% specimens, from 3rd intercostals space in 20.7% cases. The ICBN communicated more frequently with medial cutaneous nerve of the arm (MCN) in 63% cases and with other BP branches in 44.6% cases. Conclusion: In the present study we observed ICBN and BP are coherently linked anatomically. The anatomical knowledge of ICBN origin and its variable communication with BP branchesis significant in the event of surgical treatment of breast cancers, lymph node clearance, anaesthetic nerve blocks and traction injuries to the brachial plexus. Asian Journal of Medical Sciences Vol.9(5) 2018 77-80